Pengaruh Massa Bioadsorben dari Klobot Jagung Terhadap Penurunan Kandungan Asam Lemak Bebas (FFA), Nilai Peroksida (PV) dan Tingkat Warna Dalam Minyak Sawit Mentah (CPO) - Yustinah, Yustinah; Susanty, Susanty; Hendrawati, Tri Yuni; Fithriyah, Nurul Hidayati; Cardosh, Syafira R (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2023)
Indonesia as an agricultural country, produces many agricultural products. In addition to agricultural products, agricultural waste is also generated throughout the year. This agricultural waste is still underutilized. One of the efforts to utilize agricultural waste is to process agricultural waste into bioadsorbent. This study aims to study the effect of the mass of bioadsorbent from agricultural waste, namely corn husks on reducing levels of free fatty acids (FFA), peroxide value (PV) and color in crude palm oil (CPO). Clean corn husks are then mashed, after which it is reacted with NaOH to remove the lignin content and neutralized with HCl, so that a bioadsorbent is obtained. Crude palm oil is heated to 80 oC, then mixed with 2 to 10 grams of bioadsorbent according to the variables used. The mixture was stirred at 500 rpm for one hour, and the temperature was maintained at 80 oC. After the adsorption process is complete, the mixture is filtered using a vacuum pump and the filtrate is taken. The filtrate obtained was analyzed for free fatty acid content, peroxide value and color. The research resulted in the more mass of bioadsorbent used, the greater the decrease in free fatty acid levels, peroxide value and color. Using 10 g of bioadsorbent can reduce FFA levels by 41.29%, reduce PV values by 54.96% and reduce color absorbance by 29.06%.